Heterogeneous Returns to Active Labour Market Programs for Indigenous Populations - Donna L. Feir; Kelly Foley; Maggie E. C. Jones (Institute of Labor Economics (IZA), 2022)
This paper studies the impact of active labour market programs for institutionally distinct Indigenous populations in Canada using administrative data on the universe of participants in the Aboriginal Skills and Employment Training Strategy (ASETS). Within Indigenous population groups, we compare labour market outcomes among individuals who participated in high- relative to low-intensity programs, where high-intensity programs were longer in duration. For Metis and non-Status First Nations groups, we find a large impact of high-intensity participation on earnings two years post-ASETS. The post-program earnings of Status First Nations individuals who participated in high-intensity programs were not statistically different from those in low-intensity programs. We argue that these differences are due to the unique institutional environments affecting different Indigenous populations.
Keywords: J15; I38; M53; 330; administrative data; on-reserve employment; Indigenous peoples; labour market institutions; active labour market programs; program evaluation